Leadership in Catholic Social Teaching - Marek, Agnieszka (Annales. Etyka w Życiu Gospodarczym, 2015)
The material subject of Catholic social science is man and his actions taken in the fields of politics, the economy and society. According to its rules each person should be engaged in building the world through the realization of his or her vocation. One kind of vocation might be leading people by acting in accordance with the Gospel and teachings of the Church. The most important values for the leader in this case would be: respect for human dignity and human rights, freedom, justice, the subsidiarity principle and cooperation due to creating the common good. The listed rules are realized by servant leadership, the idea functioning in the field of management that derives its origins from Christ’s speech: whosoever will be chief among you, let him be your servant (Mt 20:27).